Optimal design for inspection and maintenance policy based on the CCC chart - Chan, Ling-Yau; Wu, Shaomin (Elsevier Science B.V., Amsterdam., 2009)
In this paper, the concept of cumulative count of conforming chart (CCC chart) is applied in inspection and maintenance planning for systems where minor inspection, major inspection, minor maintenance and major maintenance are available. Several inspection and maintenance plans are defined and studied quantitatively. Analytic expressions of relevant statistics and their expectations are derived. These inspection and maintenance plans are optimized from an economic consideration.
Keywords: Maintenance; Manufacturing; Fraction nonconforming; Economic design